Ilmu Gizi dan diet: hubungannya dengan penyakit-penyakit untuk perawat dan dokter/ Mary E.Beck;editor & penerjemah Andri Hartono, kristiani. - BECK MARY E; Andri Hartono; kristiani (Andi, 2011)
vi, 345hlm.: ilus.; 23cm.(3 eks)